2020
DOI: 10.13171/mjc10702007221459jek
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antioxidant activity of Ammi visnaga L. polyphenols from the Middle Atlas in Morocco

Abstract: <p>In this work, we are interested in both the study of the phenolic compounds and the evaluation of the antioxidant properties of the extracts of <em>Ammi visnaga L. </em>collected from the Middle Atlas in Morocco. Phytochemical screening was carried out to highlight the qualitative composition of the secondary metabolites contained in this plant. Also, the extraction of total polyphenols was carried out by maceration using hydromethanolic and hydroacetonic mixtures. Then, the fractionation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Our results revealed a lower or a relatively low content of total phenols, flavonoids, and condensed tannins (TPC = 7.26 ± 1.68 mg GAE/g extract; TFC = 5.82 ± 0.79 mg QE/g extract; CT = 15.08 ± 1.76 mg CE/g extract). El Karkouri et al recently analyzed the same Moroccan species, and reported similar values to ours (of 7.16 mg GAE/g) for the crude extract obtained by Soxhlet extraction in methanol 70%, and lower values for the crude extract obtained by hydro-acetone, hydro-methanol, and Soxhlet extraction in ethanol [46]. Conversely, other studies analyzing the composition of the ethanolic and methanolic extracts of A. visnaga L. have reported higher TP, TF, and CT contents comparatively with our results, although this may partially be caused by the differences between extracts and essential oil [47,48].…”
Section: Discussionsupporting
confidence: 86%
“…Our results revealed a lower or a relatively low content of total phenols, flavonoids, and condensed tannins (TPC = 7.26 ± 1.68 mg GAE/g extract; TFC = 5.82 ± 0.79 mg QE/g extract; CT = 15.08 ± 1.76 mg CE/g extract). El Karkouri et al recently analyzed the same Moroccan species, and reported similar values to ours (of 7.16 mg GAE/g) for the crude extract obtained by Soxhlet extraction in methanol 70%, and lower values for the crude extract obtained by hydro-acetone, hydro-methanol, and Soxhlet extraction in ethanol [46]. Conversely, other studies analyzing the composition of the ethanolic and methanolic extracts of A. visnaga L. have reported higher TP, TF, and CT contents comparatively with our results, although this may partially be caused by the differences between extracts and essential oil [47,48].…”
Section: Discussionsupporting
confidence: 86%
“…According to a recent study conducted by El Karkouri et al in 2020, the crude extract of A. visnaga L. polyphenols obtained from Morocco’s Middle Atlas using Soxhlet extraction with 70% methanol yielded a content of 7.16 mg GAE per gram of phenolic components. This finding provides specific information on the phenolic content of the crude extract derived from A. visnaga L. in the mentioned geographical region, highlighting its potential phenolic composition and content [ 56 ]. The findings suggest the efficacy of alcoholic solvents for phenolic compound extraction, promoting safe human consumption [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decoction prepared from the fruits of the A. visnaga had the ability to reduce blood glucose level by 51% in normoglycemic rats, compared to an oral hypoglycaemic agent (khalil et al,2020). The aqueous extract of A. visnaga possess significant hypoglycemic effect in both normal and STZ diabetic rats (El Karkouri et al,2020). Data in Table ( 7) serum protein fractions (T.protein, albumin & globulin) of all experimental groups.…”
Section: Table (1): Effect Of Feeding With Khella Baladi On Body Weight Gain (Bwg %) Feed Intake (Fi) and Feed Efficiency Ratio (Fer) Of mentioning
confidence: 97%